Impact of Economic Value Added (EVA) on financial performance - Muraleetharan, P.; Kosalathevi, T. (South Asian Academic Research Journals, 2014)
Banking industry in Sri Lanka is very important sector in economy. Most of the public and private sector banks in our country have already started looking at their portfolio of services offered and what they should do in the future for remaining competitive in the industry. However mostly private sector banks are effectively than public banks. Bankers now will have to constantly seek to invest in technology and able to be open to strategic alliance, merger, acquisition and restructuring exercises for adding EVA to shareholders wealth all the time. According the data analysis, the result of the research is Economic Value Added impact on financial performance. Financial performance indicators are Return on Equity, Return on Assets, Return on Investment and Liquid assets to liabilities. The study finds Economic value added and financial performance are statistically significant in determining performance. Perhaps most importantly, the study finds positive relationship between Economic value added and financial performance. The study provides bank managers with understanding of activities that would enhance their bank’s financial performances. The results of this study imply that it might be necessary for a bank management to take all the required decisions to enhance the financial positions of the bank.
Keywords: Economic value added; Return on equity; Liquidity; Financial performance